No Cadinho da Reconciliação: o diálogo cristão-judaico, do Parlamento Mundial das Religiões ao Vaticano II - Martins, Angelina Carr Ribeiro (2016)
The Declaration Nostra Aetate was a document that marked the opening and to the Church for interreligious dialogue, and was the turning point in relations with Jews and Judaism. It was developed in the Vatican II, and in the words of Pope John XXIII, the time was the aggiornamento or Church reform. In this process, understanding the concept of dialogue, to the Vatican, also underwent an evolution that was considered a key element in inter-religious relations of the twentieth century. Therefore, due to the Council, the Catholic Church broke with the theological paradigm supersessionism, there was a change Replacement Model for model Complementation in a new, more liberal and flexible attitude. Thus opened the way for the Christian Theology of Religions. However, the development of the content of Nostra Aetate was the result of research, publications and conferences even before the Council, both of representatives of Judaism, as for Christians, Catholics and Protestants. In this sense, the context of World War II, the Shoah and the creation of the State of Israel was decisive for the subject of the Jews were inserted in the Vatican. The most defended argument referred to the issue of teaching of contempt, led by the French Jewish historian Jules Isaac, by which the Church had to deal with religious anti-Semitism present for centuries in its liturgy. Until its enactment was an intense work in the Council backstage, both by those who opposed the theme of the Jews, as the conservative wing and the Eastern Catholic Churches, who raised political issues involving the State of Israel, as the commitment of priests, as Agostinho Bea, John Oesterreicher e Gregory Baum, with renovator spirit whose work involved skill, knowledge, diplomacy and perseverance until the Council's more political text was completed and approved, the Nostra Aetate